2021 IEEE International Conference on Cyber Security and Resilience (CSR) 2021
DOI: 10.1109/csr51186.2021.9527966
|View full text |Cite
|
Sign up to set email alerts
|

DAHID: Domain Adaptive Host-based Intrusion Detection

Abstract: Cybersecurity is becoming increasingly important with the explosion of attack surfaces as more cyber-physical systems are being deployed. It is impractical to create models with acceptable performance for every single computing infrastructure and the various attack scenarios due to the cost of collecting labeled data and training models. Hence it is important to be able to develop models that can take advantage of knowledge available in an attack source domain to improve performance in a target domain with lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Research studies have indicated that SVM and DT are among the most promising methods for anomaly detection. SVM and DT algorithms have been widely used in HIDSs due to their effectiveness in detecting and classifying intrusions [29][30][31]. In the context of HIDSs, SVM can learn the patterns and characteristics of known attacks and identify similar patterns in real-time system behavior, enabling the detection of unknown or novel attacks [29].…”
Section: Methods Description Limitationsmentioning
confidence: 99%
“…Research studies have indicated that SVM and DT are among the most promising methods for anomaly detection. SVM and DT algorithms have been widely used in HIDSs due to their effectiveness in detecting and classifying intrusions [29][30][31]. In the context of HIDSs, SVM can learn the patterns and characteristics of known attacks and identify similar patterns in real-time system behavior, enabling the detection of unknown or novel attacks [29].…”
Section: Methods Description Limitationsmentioning
confidence: 99%
“…With the exception of [14], none of the related works discussed in this section provides a comparable cross-domain evaluation of the proposed NIDS across different benchmark datasets. While the methods proposed in [15] and [16] apply domain adaptation techniques on network intrusion detection datasets, they are fundamentally different to our approach, since they rely on the availability of target domain labels, which are difficult to obtain in real-world networks. In contrast, our method proposed in this paper does not require target domain labels, and is hence much more practical.…”
Section: Partially Different Domainsmentioning
confidence: 99%
“…While these previous studies do not require labelled data from the target domain, the next two studies need a small portion of the target domain to have labels. The first paper in this group [15] considers a host-based intrusion detection approach, rather than network intrusion detection, and aims to reduce the number of labelled samples from the target domain. The authors use two different host-based intrusion detection datasets as the source and target domains respectively.…”
Section: Separate Source and Target Domainsmentioning
confidence: 99%
“…For the experiments with the Data Augmentation (DA), we process the images as recommended in [4]. For the cybersecurity task, we applied N-Gram data preprocessing, which is commonly used in [29,30]…”
Section: Target Modelmentioning
confidence: 99%